Public Perception of the Dissemination of Information on Soppeng Regency Regional Regulation - Razak, Fitriani Sari Handayani; Amiruddin, Ahmad; Faisal, Andi Fahri; Nuraliah, Dewi; Nasiruddin, Nurfadilah (Journal of Social and Policy Issues, 2024)
This study aims to analyze public perception of the dissemination of information on Regional Regulations (Perda) passed by the Soppeng Regency DPRD together with the local government. Regional regulations are legal instruments that regulate various aspects of social and economic life in the regions, but their success is highly dependent on community understanding and participation. A quantitative descriptive method was used in this study, involving 100 respondents in Soppeng Regency. Respondents are selected purposively based on the criteria of having knowledge or experience related to the Regional Regulation.  The results of the study show that 97% of the public understands the functions and duties of the DPRD, but only 43% feel that they receive information about the Regional Regulation clearly and comprehensively. Social media is the main source of information, while direct socialization by DPRD members is not optimal. The majority of people (96%) consider that the Regional Regulation is made for the benefit of the people, even though they state the need to increase the intensity of socialization. Community participation in socialization activities is still low, with 46% rarely participating in these activities. This study also found that age, education, and employment factors affect people's perception of the Regional Regulation. Respondents with higher education levels tend to have a better understanding. These findings highlight the need for intensification of socialization by the DPRD through a more inclusive strategy and the use of digital media to increase public understanding and their participation in the implementation of the Regional Regulation. Conclusion This study provides strategic recommendations to increase public involvement in the legislative process and the dissemination of legal information.  Keywords: Community Perception, Information Distribution, Regional Regulation, Soppeng Regency, Community Participation.